Sejarah, Bahasa, dan Kekuasaan: Wacana Etnisitas dalam Historiografi Indonesia - Fadly Rahman (Universitas Gadjah Mada, 2013)
When ethnology was institutionalized, it became a politic of knowledge by the colonial power. Many of the texts and images were published in the form of monographs, maps, dictionaries and even Bible form. Ethnic identity was mapped. Today the construction of ethnicity is important. In Indonesia ethnicity is a sensitive issue. Bias, stereotype and interethnic conﬂict often happens throughout the history of Indonesia. This paper tries to analyze the connection between history, language, and political power as an early construction of ethnic identity in Indonesia by tracing works in Indonesia historiography.